The Representation of Behavioral Choice for Motion in Human Visual Cortex - Serences, John T. (J Neurosci, 2007)
Single-unit recording studies have demonstrated a close link between neural activity in the middle temporal (MT) area and motion perception. In contrast, researchers using functional magnetic resonance imaging and multivoxel pattern analysis methods have recently documented direction-specific responses within many regions of the visual system (e.g., visual cortical areas V1–V4v) not normally associated with motion processing. Our goal was to determine how these direction-selective response patterns directly relate to the conscious perception of motion. We dissociated neuronal responses associated with the perceptual experience of motion from the physical presence of motion in the display by asking observers to report the perceived direction of an ambiguous stimulus. Activation patterns in the human MT complex closely matched the reported perceptual state of the observer, whereas patterns in other visual areas did not. These results suggest that, even when selective responses to a given feature are distributed relatively broadly across the visual system, the conscious experience of that feature may be primarily based on activity within specialized cortical areas.